Evaluation of an inducible knockout system in insect cells based on co-infection and CRISPR/Cas9. - Christina Sophie Hausjell; Miriam Klausberger; Wolfgang Ernst; Reingard Grabherr (PLoS ONE)
Due to comparably high product titers and low production costs, the baculovirus/insect cell expression system is considered a versatile production platform in the biopharmaceutical industry. Its excellence in producing complex multimeric protein assemblies, including virus-like particles (VLPs), which are considered promising vaccine candidates to counter emerging viral threats, made the system even more attractive. However, the co-formation of budded baculovirus during VLP production poses a severe challenge to downstream processing. In order to reduce the amount of budded baculovirus in the expression supernatant we developed an inducible knockout system based on CRISPR/Cas9 and co-infection with two baculoviral vectors: one bringing along the Cas9 nuclease and the other one having incorporated the sequence for sgRNA expression. With our set-up high titer viruses can be generated separately, as only when both viruses infect cells simultaneously a knockout can occur. When budding essential genes gp64 and vp80 were targeted for knockout, we measured a reduction in baculovirus titer by over 90%. However, as a consequence, we also determined lower overall eYFP fluorescence intensity showing reduced recombinant protein production, indicating that further improvements in engineering as well as purification are required in order to ultimately minimize costs and timeframes for vaccine production utilizing the baculovirus/insect cell expression system.